Respon Pertumbuhan Tanaman Kentang (Solanum tuberosum L.) Varietas Granola Secara In Vitro dengan Penambahan NAA dan BAP - Pandia, Wajib (JURNAL AGROTEKNOSAINS, 2023)
The low production of potatoes in Indonesia is caused by the inadequate availability of quality potato seeds from conventional methods. The tissue culture method is able to produce quality and virus-free seeds, in large quantities and in a short time. This study aims to obtain the best concentrations of NAA (Naphthalene Acetic Acid) and BAP (6-benzylaminopurine) in various explants for the growth of potato shoots (Solanum tuberosum L.) Granola variety in vitro. The research was conducted at UPT Seed Main Kutagadung Berastagi, Karo Regency from February to May 2023. The explants used were leaves taken from potato seed sprouts in vitro. The research was conducted using a Completely Randomized Design (CRD) consisting of 12 treatments and repeated 4 times. The treatments tested consisted of: A (without growth regulator); B (0.5 mg/l NAA), C (1 mg/l NAA), D (1mg/l BAP); E (1.5 mg/l BAP);F (2 mg/l BAP); G (0.5 mg/l NAA + 1 mg/l BAP); H(0.5 mg/l NAA + 1.5 mg/l BAP);I (0.5 mg/l NAA + 2 mg/l BAP); J (1 mg/l NAA + 1mg/l BAP);K (1 mg/l NAA + 1.5 mg/l BAP); L (1 mg/l NAA + 2.0 mg/l BAP). The results showed that the concentration of BAP 1 mg/l was the best treatment in producing the number of shoots, branches, leaves and nodes in intercalary meristem explants. Giving NAA (Napthelene Acetic Acid) in MS media had a significant effect. Furthermore, giving a combination of NAA and BAP did not have a real effect on all the observed parameters measured.